Chapter 9: Climate Change 2022: Impacts, Adaptation and Vulnerability Contribution of Working Group II to the IPCC Sixth Assessment Report - Intergovernmental Panel on Climate Change (Cambridge University Press, 2023)
Africa is one of the lowest contributors to greenhouse gas emissions causing climate change, yet key development sectors have already experienced widespread losses and damages attributable to human-induced climate change, including biodiversity loss, water shortages, reduced food production, loss of lives and reduced economic growth (high confidence).